The performance of co-operative organizations in Kelantan: A case study of Koperasi Kakitangan & Keluarga Air Kelantan Bhd / Norshazlin Zakaria - Zakaria, Norshazlin (Faculty of Business and Management, 2008)
This study is to evaluate the actual performance and how beneficial co-operative organizations towards its members, employees, customers, suppliers and others cooperatives as well as to the larger society. The co-operative performance can be done by analyzing the annual report or financial statement from a year to year. The measurements used in this study are ratio analysis, comparative financial statement analysis and common-size financial statement analysis to reveal the information and identify the problem occurred in the company. From the study, there are problems occurred within this organization such as, the duration of collection period is too long, the low gross and net profit margin, the low total inventory turnover, also high in cost of sales that lead to lower gross profit and net profit for the company. Besides that, the company also incurred high administration expenses that will lead to low net profit for the year. Therefore, the researcher comes out with a few recommendations to the company such as to upgrade the way of monitoring the sales and receivable. The company also needs to find the best supplier that can supply the materials with a lower cost. These recommendations will help the company to have a lower cost of sales and increase the net profit for the year.